Right Atrial Fibroelastoma Presenting as Typical Atrial Flutter: Rare Disease in Unusual Location - Ahmad Abuarqoub; Ghada Elshimy; Muhammed Shittu; Aiman Hamdan; Fayez Shamoon (Case Reports in Cardiology)
Typical atrial flutter as initial presentation of papillary fibroelastoma involving the cavotricuspid isthmus is not described before in literature. To our knowledge only 14 cases have been reported in literature involving the right atrium. Very unusual location is at the junction between inferior vena cava (IVC) and right atria as only 1 case has been reported.